Anti-adhesion methods as novel therapeutics for bacterial infections. Issue 12 (December 2012) - Cozens, Daniel; Read, Robert C
Anti-adhesion therapies for bacterial infections offer an alternative to antibiotics, with those therapies bacteria are not killed but are prevented from causing harm to a host by inhibiting adherence to host cells and tissues, a prerequisite for the majority of infectious diseases. The mechanisms of these potential therapeutic agents include inhibition of adhesins and their host receptors, vaccination with adhesins or analogs, use of probiotics and dietary supplements that interfere with receptor–adhesin interactions, subminimal inhibitory concentrations of antibiotics and manipulation of hydrophobic interactions. Once developed, these drugs will contribute to the arsenal for fighting infectious disease in the future, potentially subverting antibiotic resistance.